Pregunta
upstudy study bank question image url

Solve the equation by completing the square and applying the square root property, \[ 3 x^{2}=4=2 x \]

Ask by Harris Nichols. in the United States
Feb 19,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The solutions are \( x = \frac{1 + \sqrt{13}}{3} \) and \( x = \frac{1 - \sqrt{13}}{3} \).

Solución

We begin with the equation   3x² – 2x – 4 = 0. Step 1. Isolate the quadratic and linear terms by moving the constant to the other side:   3x² – 2x = 4 Step 2. Divide every term by 3 so that the coefficient of x² becomes 1:   x² – (2/3)x = 4/3 Step 3. Complete the square. To complete the square for x² – (2/3)x, take half of the coefficient of x (which is –2/3), namely –(2/3)/2 = –1/3, and square it:   (–1/3)² = 1/9 Add 1/9 to both sides:   x² – (2/3)x + 1/9 = 4/3 + 1/9 Step 4. Simplify the right-hand side. Write 4/3 as 12/9 so that:   4/3 + 1/9 = 12/9 + 1/9 = 13/9 Now the left-hand side is a perfect square:   (x – 1/3)² = 13/9 Step 5. Use the square root property. Taking the square root of both sides gives:   x – 1/3 = ± √(13/9) = ± (√13)/3 Step 6. Solve for x by adding 1/3 to both sides:   x = 1/3 ± (√13)/3 Thus, the solutions are:   x = (1 + √13)/3  and  x = (1 – √13)/3.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

To solve the equation \( 3x^2 = 4 - 2x \), start by rearranging it to the standard form. Rewrite it as \( 3x^2 + 2x - 4 = 0 \). Next, we need to complete the square. 1. Divide everything by 3 to simplify: \[ x^2 + \frac{2}{3}x - \frac{4}{3} = 0 \] 2. Move \(-\frac{4}{3}\) to the other side: \[ x^2 + \frac{2}{3}x = \frac{4}{3} \] 3. To complete the square, take half of the coefficient of \(x\) (which is \(\frac{2}{3}\)), square it, and add it to both sides. Half of \(\frac{2}{3}\) is \(\frac{1}{3}\), and squaring it gives \(\frac{1}{9}\): \[ x^2 + \frac{2}{3}x + \frac{1}{9} = \frac{4}{3} + \frac{1}{9} \] 4. Find a common denominator for the right side: \[ \frac{4}{3} = \frac{12}{9} \Rightarrow \frac{12}{9} + \frac{1}{9} = \frac{13}{9} \] 5. Now we have: \[ \left(x + \frac{1}{3}\right)^2 = \frac{13}{9} \] 6. Take the square root of both sides: \[ x + \frac{1}{3} = \pm \frac{\sqrt{13}}{3} \] 7. Finally, isolate \(x\): \[ x = -\frac{1}{3} \pm \frac{\sqrt{13}}{3} \] So the solutions are: \[ x = \frac{-1 + \sqrt{13}}{3} \quad \text{and} \quad x = \frac{-1 - \sqrt{13}}{3} \]

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad